Experimental and Quasi-experimental Research in Clinical Linguistics and Phonetics - Mildner, Vesna (Array, 2013)
The chapter deals with research as a process of studying a phenomenon or behavior through a series of steps that include data collection, analysis, and interpretation. Research starts with research question, a problem that the investigator sets out to explore in hopes of reaching a satisfactory answer. Research design is a plan to gather, analyze, and interpret data in order to answer research questions. The type of research will depend on subjects, instruments, data collection and analysis, expected outcome, and these will, of course depend on the research question that the investigator asked to begin with. Any good experiment must be designed to test a hypothesis while at the same time meeting the requirements of reliability, validity, and replicability.